Transnational migrant nostalgia: Venezuelan memories in the city of Lima - Vega Romá, Pablo (REMHU, Revista Interdisciplinar da Mobilidade Humana, 2025)
This article analyze, from an ethnographic approach, the expressions and the role that nostalgia plays in the daily life of a group of Venezuelan migrants dedicated to street trading in the city of Lima. Based on the analysis of memories linked to three major areas – the landscape and the pace of life in the place of origin, relatives who did not migrate, and walking without being discriminated against or harassed – the main challenges faced by the Venezuelan population since their arrival in Peru are explored. The findings show that nostalgia does not reflect an abstract and idealized vision of the past, but rather appears as an aspect that allows them to critically deal with the difficult socioeconomic conditions they face in the city. Transnational memory is constructed as a collective place of enunciation to imagine a future where their living conditions are more fair and equal.